Дослідження звукового символізму (за критеріями експерименту Кента−Розанова) - Федун, Тетяна; Fedun, Tеtiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Розглянуто роль фоносемантики в сучасному мовознавстві. Систематизовано основні категорії асоціацій на основі експліцитного та імпліцитного зв’язків відповідно до теорії механізму виникнення звукосимволізму. Експериментально встановлено зв’язок між семантикою та фонетикою мовного знака. Запропоновано сфери застосування цих зв’язків./The problem of objectively-subjective character of the phenomenon of sounds origin, confirming connection: denotatum – significant – sound form) is considered in the article. The basic categories of associations are systematized accordant to the implicit and explicit connection corresponding to mechanism of sound symbolism origin. Connection between semantics and phonetics of sign of language is set due to results of psychological and philological theories. Universality of the phenomenon of phonosematism is well-proven. Forming methodology of association on the vowels of Ukrainian is scientifically reasonable and described. The results of analysis of associative experiment data questionnaire conducted within the framework of psycholinguistic research on the base of one of the special divisions are presented. Author offers the possible spheres of drawing on received results reflecting psycholinguistic.
Research of Voice Symbolism (Cordant to the Kent−Rozanov Experiment)
Федун Т. Дослідження звукового символізму (за критеріями експерименту Кента−Розанова) / Тетяна Федун // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 141-146.
Keywords: звукосимволізм; фоносемантика; звукобуква; асоціативний експеримент; синестезійна теорія; sound symbolism; phonosematism; letersound; associative experiment; synaesthetical theory